MODEL PEMBERDAYAAN MASYARAKAT SEKITAR KAWASAN HUTAN LINDUNG JOMPI KABUPATEN MUNA, PROVINSI SULAWESI TENGGARA - DASMIN SIDU (Master Program of Environmental Science, Postgraduate Program of Udayana University)
Forest as an asset of national development is really beneficial for life and livelihood. It brings benefits ecologically, culturally, and economically on condition that the forest is properly exploited. For that purpose, forest should be managed, protected, and exploited continuously for the sake of the people's welfare, not only for the present but also for the next generation. Jompi Preserved Forest Area is one of the preserved forest areas in Muna Regency, which is now in very bad condition. The people living around the forest are powerless. This research aims: to formulate a model of community empowerment adjusted to the local condition. The technique of collecting samples used is cluster sampling, covering 226 heads of family. The analysis used is correlation analysis of Rank Spearman (r5), Multiple Regression, and Path Analysis. The result of analysis shows that the people's productivity and capability are still relatively low. This condition is resulted from the physical, human, and social capitals in the community. Similarly, the low capability of the empowerment facilitators and empowerment process also contribute to this situation. The effective empowerment model for the community around the preserved forest is the one that integrates the physical, human, and social capitals, and the facilitators' capability and empowerment process to create the power that can improve the productivity and capability of the community living around the Jompi Preserved Forest Area.